2007
DOI: 10.1007/s00425-007-0559-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the structure, expression and function of Pinus radiata D. Don arabinogalactan-proteins

Abstract: A synthetic phenylglycoside (beta-GlcY) that interacts specifically with arabinogalactan-proteins (AGPs), a class of plant cell surface proteoglycans, has been used to study the spatial distribution of AGPs in the xylem tissue of radiata pine. These studies demonstrated that AGPs were located in the compound middle lamella (CML) of the newly developed tracheid. Abundant, low salt extractable AGPs were purified from xylem tissue. Monosaccharide analysis showed that arabinose and galactose were the main sugars p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 59 publications
1
19
0
2
Order By: Relevance
“…AGPs may act as cell wall plasticizers, enlarging the pectin matrix, and allowing wall extension and cell expansion [52]. Radiata pine AGPs are located in the compound middle lamella of newly developed tracheids [53]. Expression of AGPs containing FLA domains has recently been found to influence the mechanical strength of stems of the herbaceous ( Arabidopsis ) and woody ( Eucalyptus ) angiosperms [54].…”
Section: Discussionmentioning
confidence: 99%
“…AGPs may act as cell wall plasticizers, enlarging the pectin matrix, and allowing wall extension and cell expansion [52]. Radiata pine AGPs are located in the compound middle lamella of newly developed tracheids [53]. Expression of AGPs containing FLA domains has recently been found to influence the mechanical strength of stems of the herbaceous ( Arabidopsis ) and woody ( Eucalyptus ) angiosperms [54].…”
Section: Discussionmentioning
confidence: 99%
“…Arabinogalactan proteins, galacturonans, and xyloglucans are characteristic of primary cell walls in conifer xylem (Putoczki et al, 2007(Putoczki et al, , 2008Hsieh et al, 2009) while arabino-4-O-methylglucuronoxylan and O-acetyl-galactoglucomannan are the main noncellulosic polysaccharides of secondary cell walls (Melton et al, 2009). In compression wood, the amounts of xylan and mannan are reduced relative to normal wood.…”
mentioning
confidence: 99%
“…Because of their location in the cell wall and the presence of a predicted glycophosphotidyl inositol (GPI) anchor domain in many AGPs, which would localise them to the outer leaflet of the plasma membrane, it was suggested that their function is to transmit information between the cell wall and cytoplasm [120]. AGPs are believed to play an important role in tracheid differentiation [121] and pharmacological and genetic studies provide strong evidence for a link between AGP and microtubules [122][123][124]. The existence of lipid rafts in the plasma membrane or a third protein or protein complex has been suggested as physical linkers between AGPs and the microtubule cortical array [123,125].…”
Section: Arabinogalactansmentioning
confidence: 99%